PANCASILA DAN JIHAD AKADEMIK: PERAN PERGURUAN TINGGI DI YOGYAKARTA DALAM PENGUATAN IDEOLOGI PANCASILA - Fathorrahman Fathorrahman (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2021)
This article discusses the role of higher education institutions in Yogyakarta in bolstering Pancasila’s public image through academic and non-academic approaches. Through various activities to strengthen Pancasila, three universities such as UIN Sunan Kalijaga, UGM, and UNY used academic formulas such as Focus Group Discussions which involved several groups to socialize the importance of implementing Pancasila in the life of the nation and state. In addition, there are other non-academic media such as Pancasila petitions and the use of social media as a way of improving Pancasila so that the millennial generation can recognize the ideology and historical values of Pancasila. To explain the progress of the three universities, the writer presents two questions; how is the role of science played by universities to improve Pancasila? What attempts are made by tertiary institutions to inspire academic and non-academic views? This study used a qualitative approach with the form of field research (field research) which took place in Yogyakarta. In my view, what the three universities did, became an“academic jihad” which was carried out periodically and represented the seriousness of universities in Yogyakarta to uphold the principles ​​of Pancasila in people’s lives.